2002
DOI: 10.1186/1751-0147-43-107
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity of Heifers on Different Diets

Abstract: The hyperinsulinemic euglycemic clamp technique was used to investigate the effect on insulin sensitivity of 2 different diets used in practical cattle feeding in calves. Ten 4 to 5-month-old heifer calves were allocated to 2 feeding groups, LO or HI, to obtain growth rates of 400 g/day or 900 g/day. The heifers were fed and housed individually for 5 weeks. Growth rates close to calculated rates were obtained with the diets used. Weekly blood samples were collected from the jugular vein for analysis of glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Perhaps our observation indicated that the vitamin and mineral supplementation allowed heifers to better cope with the stresses of handling and fasting. Further, greater NEFA concentration at d 83 of gestation for NoVTM heifers can be interpreted as an indicator of decreased insulin sensitivity, which is characterized by increased concentrations of circulating insulin [ 44 ]. In fact, during this experiment, NoVTM heifers had greater concentrations of insulin than VTM heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps our observation indicated that the vitamin and mineral supplementation allowed heifers to better cope with the stresses of handling and fasting. Further, greater NEFA concentration at d 83 of gestation for NoVTM heifers can be interpreted as an indicator of decreased insulin sensitivity, which is characterized by increased concentrations of circulating insulin [ 44 ]. In fact, during this experiment, NoVTM heifers had greater concentrations of insulin than VTM heifers.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how diet and management affect insulin sensitivity. It has been demonstrated that dietary Cr supplementation improves insulin sensitivity [ 43 ], whereas increasing dietary energy intake had no effect on insulin sensitivity [ 44 ]. According to Smith and Crouse [ 45 ], glucose is the primary substrate for lipogenesis in IMF tissue, so increased insulin resistance or decreased glucose uptake by the action of GLUT4 in adipose cells would result in less glucose available for fatty acid synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Kronfeld et al [8] showed that insulin administration reduce the milk yield of dairy cows. Lactating ewes fed a restricted diet have also been found to lose weight and to have a decreased GDR [16]. Furthermore, reduction of insulin sensitivity during early lactation in cows results in reduced keratin formation of the hoof via diminished absorption of Glu and amino acids [17].…”
mentioning
confidence: 99%
“…An increasing plasma NEFA concentration is the result of loss of body fat due to a negative energy balance (NEB) between energy consumption and intake [18], while increased energy consumption results in poor reproductive performance and fatty liver [6]. Increased plasma NEFA concentrations, meanwhile, can cause abnormal glucose tolerance as a result of insulin-hyposensitivity in the liver [16]. To prevent such problems, it is important to increase DMI after parturition.…”
mentioning
confidence: 99%